Monopoly Pricing Strategies - Daniel F. Spulber (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
The design of monopoly pricing strategies is examined in a general framework with an unknown population distribution of consumer characteristics, downward-sloping, multi-unit consumer demand, and increasing marginal cost Reference point pricing is introduced and is shown to implement the profit-maximizing allocation. The design of generalized priority is extended to the unknown demand setting. Nonlinear pricing is shown to be approximately optimal for the monopolist as the number of consumers gets large
Keywords: 330